Graphical connection priming and ethics: As our sense of human connection decreases, so too does our ethical decision-making. - Macdonald, Chris (Open Science Journal, 2020)
From road rage to youtube comments, there are indications all around us that when there is some form of human disconnect, we are far from the best versions of ourselves. A recent paper revealed that the mere thought of human disconnection can weaken our morals. This paper reveals three new experiments that further explore this phenomenon. The results of experiments 1 and 2 show that an increase of unethical decision-making can be triggered via simple imagery of stickmen separated from one another. Experiment 3 suggests that the phenomenon might also be triggered with simple geometric imagery depicting the disconnection of 2D shapes.